1971
DOI: 10.1530/jrf.0.0250157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mercuric Compounds on the Maternal Transmission of Selenium in the Pregnant and Lactating Rat

Abstract: The administration of small amounts of mercuric compounds to pregnant rats, injected with 75Se in the form of selenite, markedly increased their retention of 75Se and simultaneously decreased the 75Se content in their foetuses. The 75Se concentration in the blood and liver of foetuses from these rats was much lower than in the blood and liver of foetuses from control mothers injected with [75Se]selenite only (or receiving zinc chloride instead ofmercuric chloride). Retention of 75Se in the maternal organs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 8 publications
(9 reference statements)
1
26
0
Order By: Relevance
“…Supplemental dietary selenium apparently replaces the selenium lost to intracellular mercury binding, thereby maintaining normal selenoenzyme activities. Maternal mercury exposure severely compromises the distribution of maternal selenium across the placenta (Parizek et al, 1971). However when maternal selenium status is enhanced by feeding rich levels of dietary selenium, toxic effects of methylmercury resulting in depressed selenium distribution and Selenium (Se) supplementation in the nutritionally relevant range counteracts methylmercury (MeHg) toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental dietary selenium apparently replaces the selenium lost to intracellular mercury binding, thereby maintaining normal selenoenzyme activities. Maternal mercury exposure severely compromises the distribution of maternal selenium across the placenta (Parizek et al, 1971). However when maternal selenium status is enhanced by feeding rich levels of dietary selenium, toxic effects of methylmercury resulting in depressed selenium distribution and Selenium (Se) supplementation in the nutritionally relevant range counteracts methylmercury (MeHg) toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies had shown that Na2SeOs decreases the toxicity of HgC12 injected into rats, possibly by complexation of mercury in the blood (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (1,(8)(9)(10)(11) have demonstrated that if selenium is given in equimolar doses together with mercuric mercury, this has, in the rat, a protective effect against nephrotoxicity. Selenium administration is combined with a changed distribution of mercury, with increasing amounts in blood and in liver, and an increase in total body retention of mercury.…”
Section: Selenium Interaction With Mercuric Mercury Toxicitymentioning
confidence: 99%